Pemanfaatan kelas ibu hamil dan aplikasi grup pesan pintar sebagai sarana edukasi kehamilan - Wilda Rezki Pratiwi; Nurjanna Nurjanna (Holistik Jurnal Kesehatan, 2021)
Information giving and education in pregnancy using a traditional classroom and an online education (group messaging apps)Background: The efforts to improve health during pregnancy are by using a traditional classes facility to provide knowledge and information on health during pregnancy. Most community has not known some online applications that can use at positive things as suggestions for learning or health education purposes. Researchers want to innovate with social media users: WhatsApp groups to provide information and knowledge.Purpose: To analyze the differences in knowledge, activeness, motivation and behavior when information and education in pregnancy using a traditional classroom and an online education (group messaging apps).Method: Quantitative research with the design method of quasi-experiment by pretest-posttest divided in two groups. The population was Pregnant women's with the sample of 30 participants comprising 15 participants in the control group and 15 participants in the intervention group. Location in Sidenreng Rappang regency, south Sulawesi province, Indonesia.Results: In an online education (group messaging apps) group, the variables of knowledge, activeness, motivation and action influence the use of the class of pregnant women and WhatsApp media to educate problems around pregnancy, while in the control group the results of the variables of knowledge, activeness, and motivation influence class utilization pregnant women to educate problems. Meanwhile, the action variable has no effect.In order to further increase the campaign on the importance of the participation of pregnant women in implementing pregnant women classes and be able to do it regularly by involving cadres and their familiesKeywords: Information giving; Education; Pregnancy; Traditional classroom; Online education (group messaging apps)Pendahuluan : Salah satu upaya pemerintah yaitu pemberdayaan masyarakat dengan penyelenggaraan kelas ibu hamil. Fenomena masyarakat saat ini menganggap media sosial berpengaruh negative. Namun jika pemanfaatan media sosial diarahkan kehal yang positif seperti halnya penelitian ini ingin membuat inovasi dengan pemanfaat media sosial yaitu membuat group whatsapp sebagai sarana informasi, pelayanan kepada masyarakat. sehingga akan sangat besar manfaatnya kepada masyarakat khususnya ibu hamil.Tujuan: Menganalisa perbedaaan pengetahuan, keaktifan, motivasi dan tindakan  ibu pada kelompok kelas ibu hamil dan aplikasi media whatsappMetode: Penelitian kuantitatif dengan metode  desain quasi experiment  dengan rancangan penelitian pretest- posttest two group design. Populasinya para ibu hamil dengan sampel 30 partisipan  yang dibagi 2 kelompok terdiri dari 15 partisipan  pada kelompok kontrol dan 15 partisipan pada kelompok intervensi. Lokasi di Kabupaten Sidenreng Rappang, Provinsi Sulawesi Selatan, Indonesia.Hasil : Pada kelompok kasus didapatakan hasil variabel pengetahuan, keaktifan , motivasi dan tindakan berpengaruh terhadap pemanfaatan kelas ibu hamil dan media whatsapp sebagai sarana edukasi masalah seputar kehamilan, sedangkan pada kelompok kontrol  didapatakan hasil variabel pengetahuan, keaktifan , dan motivasi berpengaruh terhadap pemanfaatan kelas ibu hamil sebagai sarana edukasi masalah seputar kehamilan.